Neurosycal Theory in The Islamic Intellectual Tradition (Critical Analysis of Historical Dimensions in Psychology) - Jarman Arroisi Arroisi; Tamia Fauziah Latifah (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2023)
Researchers have widely reviewed the study of neuroscience, but the historicity of this science is not widely known. The rapid development of modern neuroscience cannot be separated from the contributions of Muslim scientists in the Middle Ages. This paper aims to explain the history of neuroscience in the Islamic intellectual tradition and its development to influence Western civilization. For this reason, this paper uses a descriptive-analytical method with library research. The study results show that Muslim scientists such as Abu Zaid Al-Balkh, Ibn Sina, Al-Ghazali Az-Zahrawi, and Al-Razi's contribution to modern neuroscience is impressive and cannot be forgotten. As an example of research on the brain's anatomy and its disorders discussed by Vesalius and Golgi, they refer a lot to books by Ibn Sina, Al-Balkhi, and Al-Zahrawi. Rene Descartes, who discovered the theory of brain physiology, has long been discussed by Al-Razi. Even the introduction of the relationship between brain and brain function was only known in the 17th century and has long been discussed by Al-Ghazali. An original and imaginative thought regarding one of the human body’s organs, Muslims are unaware of the extensive research done on neuroscience by traditional Muslim scholars, who were able to bring Islamic culture to its pinnacle in Andalusia and Cordoba. Therefore, it is appropriate to bring the findings back into the study material with full seriousness in the form and fresh face if Muslims want to advance.